Dynamic user equipment‐based hysteresis‐adjusting algorithm in LTE femtocell networks. Issue 17 (1st November 2014) - Zhang, Xu; Xiao, Zhu; Mahato, Shyam Babu; Liu, Enjie; Allen, Ben; Maple, Carsten
Abstract : In long‐term evoluation (LTE) femtocell networks, hysteresis is one of the main parameters which affects the performance of handover with a number of unnecessary handovers, including ping‐pong, early, late and incorrect handovers. In this study, the authors propose a hybrid algorithm that aims to obtain the optimised unique hysteresis for an individual mobile user moving at various speeds during the inbound handover process. This algorithm is proposed for two‐tier scenarios with macro and femto. The centralised function in this study evaluates the overall handover performance indicator. Then, the handover aggregate performance indicator (HAPI) is used to determine an optimal configuration. Based on the received reference signal‐to‐interference‐plus‐noise ratio, the distributed function residing on the user equipment (UE) is able to obtain an optimal unique hysteresis for the individual UE. Theoretical analysis with three indication boundaries is provided to evaluate the proposed algorithm. A system‐level simulation is presented, and the proposed algorithm outperformed the existing approaches in terms of handover failure, call‐drop and redundancy handover ratios and also achieved better overall system performance.